Code switching and code mixing in English learning process - Fanani, Ahmad; Ma'u, Jean Antunes Rudolf Zico (LingTera, 2018)
The research was conducted in order to describe the types and factors of code-switching and code-mixing in the learning process. The research was a descriptive qualitative investigation using the case study method. The aim was to analyze the types and factors that caused code-switching and code-mixing. Then, the research subjects were three English teachers who taught Grade XI. In gathering the data, there were five classes that should be observed and the necessary data were gathered through recording technique. In the meantime, for validating the results of the analysis an FGD (Focus Group Discussion) should be held. The FGD was conducted in order to identify the answers to the research questions. Next, the results of the study were as follows. First, the types of code-switching were (a) intersentential code-switching, (b) intrasentential code-switching, and (c) tag-switching. On the other hand, the types of code-mixing were (a) alternation code-mixing, (b) insertion code-mixing, and (c) congruent lexicalization. Second, the factors that caused the use of code-switching in the English learning process were text quotation, clarification, and teacher’s instruction. On the other hand, the factors that caused the use of code-mixing were speech habits such as the first language and the second language effects, adversity of finding equivalent words, and people’s impression of the present trends.